Multi-layer electrolyte membrane for solid-state battery and preparation method of multi-layer electrolyte membrane

By adopting a multi-layer electrolyte membrane structure, combining the oxidation resistance and reduction resistance film layer, and the design of porous lining storage sacrificial additives, the existing battery film is easily oxidized and decomposed under high voltage and easily reduced after contact with lithium metal, achieving long-term stable operation and safety improvement of the battery.

CN119786716AActive Publication Date: 2025-04-08ZHEJIANG FUNLITHIUM NEW ENERGY TECH CO LTD

Patent Information

Application Number
CN202510014661.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-04-08
Estimated Expiration
2045-01-06

AI Technical Summary

Technical Problem

The polymer electrolyte membrane of existing solid-state batteries is easily oxidized and decomposed at high voltages, and is easily reduced after contacting lithium metal, making it difficult to take into account both oxidation and reduction resistance.

Method used

The multi-layer electrolyte membrane structure is adopted. The first layer of film has oxidation resistance, the second layer of film contains porous lining storage sacrificial additives, and the third layer of film has reduction resistance. With this structure, sacrificial additives can be gradually released during the battery cycle, providing dual protection, and improving the cycle stability and safety of the battery.

Benefits of technology

The stability of high nickel positive electrode and lithium metal negative electrode is achieved, the service life of the battery is extended, the safety and cycle stability of the battery are improved, and the performance is excellent in high temperature or high load conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119786716A_ABST
    Figure CN119786716A_ABST
Patent Text Reader

Abstract

The invention discloses a multi-layer electrolyte membrane for a solid-state battery and a preparation method thereof, and the multi-layer electrolyte membrane comprises a first layer membrane which has oxidation resistance and is used for contacting with a high-nickel positive electrode material; the second layer of film comprises a porous lining body, a sacrificial additive is stored in the porous lining body, and the sacrificial additive can be released in the cycle process of the battery; and the third-layer film has reduction resistance and is used for being in contact with a lithium metal negative electrode material. According to the invention, the electrolyte membrane with a multi-layer structure is constructed, an oxidation-resistant polymer is used for the positive electrode, and a reduction-resistant polymer is used for the negative electrode. The polymer solid electrolyte with a wide electrochemical window is constructed and can be matched with a high-nickel positive electrode and a lithium metal negative electrode at the same time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of solid-state batteries, and in particular to a multilayer electrolyte membrane for solid-state batteries and a preparation method thereof. Background Art

[0002] One of the key challenges of lithium-ion batteries is how to improve battery safety. Solid electrolytes with non-flammable and non-leakage properties are key materials to effectively improve safety issues. Solid electrolytes can be divided into two systems according to material categories: inorganic solid electrolytes and polymer solid electrolytes. Among them, polymer solid electrolytes have become ideal electrolyte materials for solid-state batteries because of their good contact interface, excellent processability, and flexibility and mechanical strength.

[0003] With the rapid development of the low-altitude economy, in addition to safety, higher requirements are also placed on the energy density of lithium batteries. High-nickel ternary positive electrode (NCM) and lithium metal negative electrode with high energy density have become ideal materials, while NCM / Li solid-state batteries have placed higher requirements on polymer solid electrolytes, which need to have both oxidation resistance and reduction resistance. Although commonly used polyethylene oxide (PEO) and polymethyl methacrylate (PMMA) have good reduction resistance, they are easily oxidized and decomposed under high voltage; while polyvinylidene fluoride (PVDF) and polyacrylonitrile (PAN) with oxidation resistance are easily reduced after contacting lithium metal. Therefore, constructing a polymer solid electrolyte with a wide electrochemical window has become a core issue.

[0004] Researchers have proposed a variety of solutions to this problem, such as constructing a composite membrane with a gradient structure and forming a CEI layer on the surface of the positive electrode particles.

[0005] In the patent application number 201810589634.3, a composite solid electrolyte membrane with a gradient distribution of inorganic electrolytes was constructed. The high content of inorganic solid electrolytes on the positive electrode side can withstand higher voltages, and the high content of polymer electrolytes on the negative electrode side can better inhibit lithium dendrites and alleviate the volume expansion of the negative electrode. The gradient design takes into account the requirements of high voltage resistance and inhibition of lithium dendrites and negative electrode volume expansion. However, increasing the content of inorganic materials is effective in improving the oxidation resistance of polymers, because polymers that are not resistant to oxidation will still be oxidized by the positive electrode.

[0006] In the patent with application number 202211029889.7, a composite solid electrolyte membrane containing a boron-containing additive and a boron-containing lithium salt is designed. During the battery cycle, the boron-containing additive will oxidize and decompose earlier than the polymer electrolyte, and lithium borate (Li3BO3) will be generated on the surface of the positive electrode particles, which prevents the layered oxide positive electrode from directly contacting the polymer electrolyte and causing catalytic oxidation, thereby solving the oxidation resistance problem of the polymer solid electrolyte membrane. However, the rupture of the CEI layer will lead to the continuous consumption of the additive, and eventually the positive electrode will come into contact with the polymer again. Summary of the invention

[0007] The purpose of the present invention is to provide a multilayer electrolyte membrane for solid-state batteries and a preparation method thereof. The main purpose is to invent a multilayer electrolyte membrane for solid-state batteries, which is characterized by having stability to high-nickel positive electrodes and lithium metal negative electrodes, and at the same time having ultra-long cycle stability.

[0008] The technical solution adopted by the present invention to solve the above technical problems is:

[0009] A multilayer electrolyte membrane for a solid-state battery, comprising:

[0010] A first film having oxidation resistance and used for contacting with a high-nickel positive electrode material;

[0011] A second membrane, the second membrane comprising a porous liner storing a sacrificial additive that can be released during battery cycling;

[0012] The third film has reduction resistance and is used for contacting with the lithium metal negative electrode material.

[0013] The above technical solution can effectively improve battery performance and provide dual protection of oxidation resistance and reduction resistance: the first and third layers of the film are resistant to oxidation and resistant to reduction, respectively, and can effectively cope with the oxidation and reduction reactions of high-nickel positive electrode and lithium metal negative electrode materials during battery cycles, ensuring long-term stable operation of the battery and extending the battery life.

[0014] Optimize battery safety: During the battery cycle, sacrificial additives can be gradually released when the battery is working, alleviating the side effects caused by battery reactions and enhancing the safety and stability of the battery, especially under high temperature or high load.

[0015] Preferably, the first film layer comprises an oxidation-resistant polymer, a lithium salt, a sacrificial additive and a plasticizer, and the third film layer comprises a reduction-resistant polymer, a lithium salt, a sacrificial additive and a plasticizer.

[0016] Preferably, the sacrificial additive is one of lithium tetrafluoroborate LiBF4 and lithium nitrate LiNO3.

[0017] By using sacrificial additives such as LiBF4 and LiNO3, controlled ion release can be provided during the battery's charge and discharge process. This feature helps to effectively avoid the risks caused by the growth of lithium dendrites or high-temperature reactions, further improving the safety and cycle stability of the battery.

[0018] The first and third layers contain sacrificial additives lithium tetrafluoroborate (LiBF4) and lithium nitrate (LiNO3), respectively. LiBF4 can form an inorganic CEI layer containing B and F on the surface of the positive electrode particles, and LiNO3 can form an SEI layer containing N on the surface of lithium metal, thereby improving the cycle performance. The sacrificial additives stored in the second layer can be supplemented to the first and third layers, ultimately achieving an ultra-long cycle stability system.

[0019] Preferably, the oxidation-resistant polymer is at least one of polyvinylidene fluoride PVDF, polyvinylidene fluoride-hexafluoropropylene PVDF-HFP, polyacrylonitrile PAN, polypropylene carbonate PPC, and polyvinyl chloride PVC; PVDF and PAN are preferred. The reduction-resistant polymer is at least one of polyethylene oxide PEO, polymethyl methacrylate PMMA, and polydimethylsiloxane PDMS; PMMA and PEO are preferred.

[0020] The lithium salt is one of lithium perchlorate LiClO4, lithium hexafluoroarsenate LiAsF6, lithium hexafluorophosphate LiPF6, lithium difluorooxalatoborate LiDFOB, lithium bis(difluorosulfonyl)imide LiFSI and lithium bis(trifluoromethylsulfonyl)imide LiTFSI; among which LiPF6, LiClO4 and LiDFOB are preferred.

[0021] The plasticizer is divided into a solid plasticizer and a functional plasticizer. The solid plasticizer is characterized in that it is solid at room temperature and is composed of at least one of ethylene carbonate EC, cyclopentane sulfone TMS, and succinonitrile SN; the functional plasticizer is one of propylene carbonate PC, dimethyl carbonate DMC, diethyl carbonate DEC, ethyl methyl carbonate EMC, 1,2-dimethoxypropane DMP, dimethoxymethane DMM, ethylene glycol dimethyl ether DME, acetonitrile ACN, trimethyl phosphate TMP, triethyl phosphate TEP, fluoroethylene carbonate FEC, vinylene carbonate VC, vinyl sulfate DTD, and 1,3-propylene sultone PST. VC, FEC, PC, and TMP are preferred.

[0022] Preferably, the porous lining is one of PE diaphragm, PP diaphragm, non-woven fabric, glass fiber membrane, and electrospun membrane, wherein the electrospun membrane is PAN or PVDF, and the thickness of the porous lining is 3 μm-30 μm, and the porosity is not less than 20%. Among them, non-woven fabric is preferred, with a thickness of 5-15 μm and a porosity of not less than 30%.

[0023] Preferably, the mass proportions of the components in the first layer of film are: the mass proportion of the oxidation-resistant polymer is 8% to 22.5%, the mass proportion of the lithium salt is 7.5% to 12%, the mass proportion of the sacrificial additive is 0.5% to 5%, and the mass proportion of the plasticizer is 70% to 80%;

[0024] The mass proportions of the components in the third layer of the film are as follows: the mass proportion of the reduction-resistant polymer is 8% to 22.5%, the mass proportion of the lithium salt is 7.5% to 12%, the mass proportion of the sacrificial additive is 0.5% to 5%, and the mass proportion of the plasticizer is 70% to 80%.

[0025] By adopting the above technical scheme, the multilayer membrane structure described in the present invention can effectively improve the ionic conductivity of the solid electrolyte membrane. The polymer of the first layer of the membrane has good oxidation resistance and matches the high-nickel positive electrode. The polymer of the third layer of the membrane has good reduction resistance and can match the lithium metal negative electrode. In the application of high-nickel positive electrode materials and lithium metal negative electrodes, it has better ion conductivity, thereby improving the battery's charge and discharge efficiency and capacity retention rate.

[0026] By precisely controlling the materials and composition ratios of each layer of the membrane, the electrolyte membrane has good mechanical strength and chemical stability, reducing membrane damage or performance degradation caused by stress changes or environmental factors during battery charging and discharging.

[0027] In the present invention, the first layer of membrane includes an oxidation-resistant polymer, a lithium salt, a sacrificial additive - lithium tetrafluoroborate and a plasticizer, the second layer of membrane includes a porous liner and a sacrificial additive, and the third layer of membrane includes a reduction-resistant polymer, a lithium salt, a sacrificial additive - lithium nitrate and a plasticizer.

[0028] A method for preparing a multilayer electrolyte membrane for a solid-state battery, for preparing the multilayer electrolyte membrane, comprises the following steps:

[0029] S1. Prepare the first layer of film by tape casting: add oxidation-resistant polymer, lithium salt, sacrificial additive and plasticizer into a sealed stirring tank according to mass ratio, control the temperature and stir evenly to obtain a first slurry, pour the first slurry into a material box of a tape casting machine, use a tape casting machine to cast and shape, and obtain the first layer of film after solidification.

[0030] In the first slurry, the polymer and lithium salt components account for 20%-30% of the total mass, preferably 24%-28%, the polymer accounts for 40%-75% of the total mass of the polymer and lithium salt components, preferably 50%-60%. The plasticizer accounts for 70%-80% of the total mass, preferably 72%-76%, and the solid plasticizer accounts for 85%-100% of the total mass of the plasticizer, preferably 89%-94%.

[0031] S2, preparing the second layer of membrane: adding the sacrificial additive and the solvent into a stirring tank and stirring evenly to obtain a second slurry, and using a casting machine to cast the second layer of membrane on the porous liner;

[0032] The solvent is DME, ACN, acetone (AC), ethanol (ET), N-methylpyrrolidone (NMP), among which DME is preferred. The slurry is a white turbid liquid or a colorless transparent solution, with a solid content of 1%-30%, among which 10% is preferred. The stirring speed is 100-2000rpm, and the stirring time is 10-60min. The stirring speed is preferably 100-300rpm; the stirring time is preferably 30min.

[0033] S3, preparing the third layer of film by tape casting: adding the reduction-resistant polymer, lithium salt, sacrificial additive and plasticizer into a sealed stirring tank according to the mass ratio, controlling the temperature and stirring evenly to obtain the third slurry, and then using a tape casting machine to tape cast to obtain the third layer of film;

[0034] S4, stacking the first membrane, the second membrane and the third membrane and performing hot rolling to obtain a multilayer electrolyte membrane.

[0035] The preparation method provided by the present invention combines the tape casting method with the hot rolling technology, which not only simplifies the preparation process of the membrane and reduces the production cost, but also ensures that the thickness of each layer of the membrane is uniform and the film quality is excellent, thereby improving the performance of the overall electrolyte membrane. The method has good operability and industrial feasibility, can adapt to the production needs of different scales, and has broad commercial application prospects.

[0036] Preferably, the stirring temperature in step S1 and step S3 is controlled at 100°C-180°C.

[0037] The stirring tank is characterized by being sealable, heatable and stirrable. The stirring speed is 100-2000rpm, the stirring temperature is 100℃-180℃, and the stirring time is 30min-180min. The stirring speed is preferably 900-1000rpm, the stirring temperature is preferably 110-140℃; and the stirring time is preferably 120min.

[0038] Preferably, in step S1 and step S3, the temperature of the material box of the casting machine needs to be consistent with the stirring temperature, the scraper gap of the casting molding is controlled to be 3μm-400μm, the tape speed is 0.05m / min-1m / min, preferably 0.5m / min, and the slurry is cooled after casting to solidify into a film. The cooling method includes natural cooling or semiconductor cooling. The setting temperature of the semiconductor cooling is -10℃-10℃. The cooling method and cooling temperature are matched with the tape speed to ensure that the slurry is solidified into a film before winding; in step S2, the scraper gap of the casting molding is controlled to be 0-50μm, preferably 5μm, the tape speed is 0.05m / min-2m / min, preferably 1m / min, and the drying temperature is 60-100℃, preferably 80℃, and the second layer of film is obtained after drying.

[0039] Preferably, during the hot rolling process, the first and third film layers soften, penetrate into the gap of the second film layer under pressure and are tightly combined. The hot rolling speed is 0.05m / min-1m / min, preferably 0.54m / min. The softening of the polymer film is achieved by controlling the roller temperature. The roller temperature is 60℃-140℃, preferably 100℃, and the reduction rate is 10%-90%.

[0040] Compared with the prior art, the advantages of the present invention are:

[0041] 1. The present invention constructs a multi-layer electrolyte membrane, using an oxidation-resistant polymer for the positive electrode and a reduction-resistant polymer for the negative electrode. A polymer solid electrolyte with a wide electrochemical window is constructed, which can simultaneously match the high-nickel positive electrode and the lithium metal negative electrode; the second layer of the membrane is a porous liner with excellent mechanical strength, which can store sacrificial additives while improving the mechanical strength of the composite membrane.

[0042] 2. The present invention uses sacrificial additives to form CEI and SEI layers on the surface of positive electrode particles and lithium metal negative electrode to improve cycle stability. At the same time, additional sacrificial additives are stored in the second layer of the film, and the additives are supplemented to the first and third layers of the film through diffusion to achieve an ultra-long cycle life.

[0043] 3. The present invention uses hot pressing to complete the assembly of the multilayer structure in one step, and the process steps are simple and efficient. At the same time, heat treatment improves the interface between the multilayer structures and reduces the internal resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0045] Figure 1 The present invention is a flow chart for preparing a multilayer electrolyte membrane for solid-state batteries.

[0046] Figure 2 Schematic diagram of the structure of the multilayer electrolyte membrane for solid-state batteries in the present invention.

[0047] Figure 3 This is the cycle performance diagram (0.2 / 0.5C) of the multilayer electrolyte membrane composition NCM811 / Li soft pack in the present invention. DETAILED DESCRIPTION

[0048] The technical solution of the present invention will be clearly and completely described below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments.

[0049] Embodiment 1,

[0050] A method for preparing a multilayer electrolyte membrane for a solid-state battery comprises the following steps:

[0051] The first layer of membrane was prepared by tape casting: PVDF, LiPF6, LiBF4, TMS, and VC were added into a sealed stirring tank in a mass ratio of 14%: 10%: 4%: 67%: 5%, with a rotation speed of 900 rpm and heating and stirring at 110°C for 120 minutes. Then, the slurry was poured into a material box at 110°C and cast into a film using a tape casting machine. The scraper gap was 120 μm, the tape speed was 0.5 m / min, and the cooling method was natural cooling to obtain the first layer of membrane.

[0052] Preparation of the second layer of membrane: LiBF4, LiNO3 and DME were added into a stirring tank in a mass ratio of 5%:5%:90%, with a rotation speed of 250 rpm and stirring at room temperature for 30 min. A 12 μm non-woven fabric was used as a lining, and a casting machine was used to cast the slurry into a membrane. The scraper gap was 5 μm, the belt speed was 1 m / min, and the hot air drying temperature was 80°C to obtain the second layer of membrane.

[0053] The third layer of membrane was prepared by tape casting: PEO, LiPF6, LiNO3, TMS, and FEC were added into a sealed stirring tank in a mass ratio of 14%: 10%: 4%: 67%: 5%, heated and stirred at 900rpm and 110°C for 120min, then the slurry was poured into a material box at 110°C, and a tape casting machine was used to cast the film, the scraper gap was 120μm, the tape speed was 0.5m / min, and the cooling method was natural cooling to obtain the third layer of membrane.

[0054] The first membrane A, the second membrane B, and the third membrane C were stacked and hot rolled at a rolling speed of 0.5 m / min, a rolling temperature of 100° C., and a reduction rate of 60% to obtain a multilayer electrolyte membrane, which was recorded as sample 1.

[0055] Comparative Example 1

[0056] The invention discloses preparing an electrolyte membrane, comprising the following steps:

[0057] A film: PVDF, LiPF6, LiBF4, TMS, and VC were added into a sealed stirring tank in a mass ratio of 14%:10%:4%:67%:5%, heated and stirred at 900rpm and 110°C for 120min, then the slurry was poured into a material box at 110°C, and cast into a film using a casting machine with a blade gap of 120μm and a tape speed of 0.5m / min. The cooling method was natural cooling to obtain A film.

[0058] B membrane: 12μm non-woven fabric is used as the lining.

[0059] C film: PEO, LiPF6, LiNO3, TMS, and FEC were added into a sealed stirring tank in a mass ratio of 14%:10%:4%:67%:5%, heated and stirred at 900rpm and 110°C for 120min, then the slurry was poured into a material box at 110°C, and cast into a film using a casting machine with a blade gap of 120μm and a tape speed of 0.5m / min. The cooling method was natural cooling to obtain a C film.

[0060] The A, B, and C membranes were stacked and hot rolled at a rolling speed of 0.5 m / min, a rolling temperature of 100° C., and a reduction rate of 60% to obtain a multilayer electrolyte membrane, which was recorded as Sample 2.

[0061] Comparative Example 2

[0062] The invention discloses preparing an electrolyte membrane, comprising the following steps:

[0063] A film: PVDF, LiPF6, LiBF4, TMS, and VC were added into a sealed stirring tank in a mass ratio of 14%:10%:4%:67%:5%, heated and stirred at 900rpm and 110°C for 120min, then the slurry was poured into a material box at 110°C, and cast into a film using a casting machine with a blade gap of 120μm and a tape speed of 0.5m / min. The cooling method was natural cooling to obtain A film.

[0064] B membrane: 12μm non-woven fabric is used as the lining.

[0065] C membrane: PVDF, LiPF6, LiNO3, TMS, and FEC were added into a sealed stirring tank in a mass ratio of 14%:10%:4%:67%:5%, heated and stirred at 900rpm and 110°C for 120min, then the slurry was poured into a material box at 110°C, and cast into a film using a casting machine with a blade gap of 120μm and a tape speed of 0.5m / min. The cooling method was natural cooling to obtain a C membrane.

[0066] The A, B, and C membranes were stacked and hot rolled at a rolling speed of 0.5 m / min, a rolling temperature of 100° C., and a reduction ratio of 60% to obtain a multilayer electrolyte membrane, which was recorded as Sample 3.

[0067] Comparative Example 3

[0068] A film: PEO, LiPF6, LiBF4, TMS, and VC were added into a sealed stirring tank in a mass ratio of 14%:10%:4%:67%:5%, heated and stirred at 900rpm and 110°C for 120min, then the slurry was poured into a material box at 110°C, and cast into a film using a casting machine with a blade gap of 120μm and a tape speed of 0.5m / min. The cooling method was natural cooling to obtain A film.

[0069] B membrane: 12μm non-woven fabric is used as the lining.

[0070] C film: PEO, LiPF6, LiNO3, TMS, and FEC were added into a sealed stirring tank in a mass ratio of 14%:10%:4%:67%:5%, heated and stirred at 900rpm and 110°C for 120min, then the slurry was poured into a material box at 110°C, and cast into a film using a casting machine with a blade gap of 120μm and a tape speed of 0.5m / min. The cooling method was natural cooling to obtain a C film.

[0071] The A, B, and C membranes were stacked and hot rolled at a rolling speed of 0.5 m / min, a rolling temperature of 100° C., and a reduction ratio of 60% to obtain a multilayer electrolyte membrane, which was recorded as Sample 4.

[0072] The above samples 1 to 4 were assembled into NCM811 / Li button batteries to test 0.33 / 0.33C cycle performance, wherein the A film / the first film layer faced the NCM811, and the C film / the third film layer faced the Li.

[0073] Table 1 shows the NCM811 / Li buckle power cycle number (0.33 / 0.33C) of samples 1 to 4

[0074] sample Cyc Capacity retention rate % Sample 1 200 98.2 Sample 2 200 87.6 Sample 3 200 80.1 Sample 4 50 <80

[0075] As can be seen from the above table, the present invention optimizes the functionality of each layer of the membrane and provides targeted protection for different battery materials (positive and negative electrodes). Specifically, when the first and third layers of the membrane are in contact with the positive and negative electrode materials, respectively, their oxidation resistance and reduction resistance can effectively prevent membrane breakage and performance degradation, thereby extending the service life of the battery. In addition, the second layer of the membrane (layer B) uses sacrificial additives (such as LiBF4, LiNO3) and is stored through a porous liner. These additives can be gradually released during the battery charging and discharging process, reducing unnecessary reactions within the battery, and in particular can effectively inhibit the growth of lithium dendrites. The formation of such dendrites can cause the battery to short-circuit, fail or overheat, thereby causing safety problems. The controlled release of sacrificial additives further improves the safety of the battery under extreme conditions such as high-rate charging and discharging, overcharging and over-discharging.

[0076] In the comparative samples, whether it is sample 2, sample 3 or sample 4, the electrolyte membrane is a single structure, that is, although the A membrane, B membrane and C membrane exist, they are not combined with the release mechanism of the sacrificial additive like in Example 1. The lack of a second layer design for storing sacrificial additives makes it impossible to actively release sacrificial additives during battery charging and discharging, making it impossible for these comparative samples to effectively control the growth and side reactions of lithium dendrites during battery use, especially at high temperatures or high rate charging and discharging, the performance of the battery will gradually decay, and there are great safety risks.

[0077] The NCM811 electrode was laminated to the first film surface of sample 1 and hot rolled at a rolling speed of 0.5 m / min, a rolling temperature of 100°C, and a reduction rate of 60% to obtain an integrated structure of a positive electrode and a multilayer electrolyte membrane. The third film surface was then assembled to form a 3Ah NCM811 / Li soft pack to test the 0.2 / 0.5C cycle performance.

[0078] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A multilayer electrolyte membrane for a solid-state battery, characterized in that: Including in order: A first film having oxidation resistance and used for contacting with a high-nickel positive electrode material; A second membrane, the second membrane comprising a porous liner storing a sacrificial additive that can be released during battery cycling; The third film has reduction resistance and is used for contacting with the lithium metal negative electrode material.

2. A multilayer electrolyte membrane for a solid-state battery according to claim 1, characterized in that: The first film layer comprises an oxidation-resistant polymer, a lithium salt, a sacrificial additive and a plasticizer, and the third film layer comprises a reduction-resistant polymer, a lithium salt, a sacrificial additive and a plasticizer.

3. A multilayer electrolyte membrane for a solid-state battery according to claim 2, characterized in that: The sacrificial additive is one of lithium tetrafluoroborate LiBF4 and lithium nitrate LiNO3.

4. A multilayer electrolyte membrane for a solid-state battery according to claim 2, characterized in that: The oxidation-resistant polymer is at least one of polyvinylidene fluoride PVDF, polyvinylidene fluoride-hexafluoropropylene PVDF-HFP, polyacrylonitrile PAN, polypropylene carbonate PPC, and polyvinyl chloride PVC; the reduction-resistant polymer is at least one of polyethylene oxide PEO, polymethyl methacrylate PMMA, and polydimethylsiloxane PDMS; The lithium salt is one of lithium perchlorate LiClO4, lithium hexafluoroarsenate LiAsF6, lithium hexafluorophosphate LiPF6, lithium difluorooxalatoborate LiDFOB, lithium bis(difluorosulfonyl)imide LiFSI and lithium bis(trifluoromethylsulfonyl)imide LiTFSI; The plasticizer is divided into a solid plasticizer and a functional plasticizer. The solid plasticizer is at least one of ethylene carbonate EC, cyclopentane sulfone TMS, and succinonitrile SN; the functional plasticizer is one of propylene carbonate PC, dimethyl carbonate DMC, diethyl carbonate DEC, ethyl methyl carbonate EMC, 1,2-dimethoxypropane DMP, dimethoxymethane DMM, ethylene glycol dimethyl ether DME, acetonitrile ACN, trimethyl phosphate TMP, triethyl phosphate TEP, fluoroethylene carbonate FEC, vinylene carbonate VC, vinyl sulfate DTD, and 1,3-propylene sultone PST.

5. A multilayer electrolyte membrane for a solid-state battery according to claim 1, characterized in that: The porous lining is one of PE membrane, PP membrane, non-woven fabric, glass fiber membrane and electrostatic spinning membrane, wherein the electrostatic spinning membrane is PAN or PVDF, the thickness of the porous lining is 3μm-30μm, and the porosity is not less than 20%.

6. A multilayer electrolyte membrane for a solid-state battery according to claim 2, characterized in that: The mass proportions of the components in the first layer of film are: the mass proportion of the oxidation-resistant polymer is 8% to 22.5%, the mass proportion of the lithium salt is 7.5% to 12%, the mass proportion of the sacrificial additive is 0.5% to 5%, and the mass proportion of the plasticizer is 70% to 80%; The mass proportions of the components in the third layer of the film are as follows: the mass proportion of the reduction-resistant polymer is 8% to 22.5%, the mass proportion of the lithium salt is 7.5% to 12%, the mass proportion of the sacrificial additive is 0.5% to 5%, and the mass proportion of the plasticizer is 70% to 80%.

7. A method for preparing a multilayer electrolyte membrane for a solid-state battery, characterized in that: The method for preparing the multilayer electrolyte membrane according to any one of claims 1 to 6 comprises the following steps: S1. Preparing the first film layer: adding the oxidation-resistant polymer, lithium salt, sacrificial additive and plasticizer into a sealed stirring tank according to the mass ratio, controlling the temperature and stirring evenly to obtain a first slurry, and then using a casting machine to cast to obtain the first film layer; S2, preparing the second layer of membrane: adding the sacrificial additive and the solvent into a stirring tank and stirring evenly to obtain a second slurry, and using a casting machine to cast the second layer of membrane on the porous liner; S3, preparing the third layer of film: adding the reduction-resistant polymer, lithium salt, sacrificial additive and plasticizer into a sealed stirring tank according to the mass ratio, controlling the temperature and stirring evenly to obtain a third slurry, and then using a casting machine to cast to obtain the third layer of film; S4, stacking the first membrane, the second membrane and the third membrane and performing hot rolling to obtain a multilayer electrolyte membrane.

8. The method for preparing a multilayer electrolyte membrane for a solid-state battery according to claim 7, characterized in that: The stirring temperature in step S1 and step S3 is controlled at 100°C-180°C.

9. The method for preparing a multilayer electrolyte membrane for a solid-state battery according to claim 7, characterized in that: In the step S1 and step S3, the temperature of the material box of the casting machine needs to be consistent with the stirring temperature. The scraper gap of the casting molding is controlled to be 3μm-400μm, and the tape speed is 0.05m / min-1m / min. After casting, the slurry is cooled to solidify into a film. The cooling method includes natural cooling or semiconductor cooling. The semiconductor cooling setting temperature is -10℃-10℃ to ensure that the slurry solidifies into a film before winding; in the step S2, the scraper gap of the casting molding is controlled to be 0-50μm, and the tape speed is 0.05m / min-2m / min.

10. The method for preparing a multilayer electrolyte membrane for a solid-state battery according to claim 7, characterized in that: During the hot rolling process, the first and third layers of the film soften, penetrate into the gap of the second layer of the film under pressure and are tightly combined. The hot rolling speed is 0.05m / min-1m / min. The softening of the polymer film is achieved by controlling the roller temperature. The roller temperature is 60℃-140℃, and the reduction rate is 10%-90%.

Citation Information

Patent Citations

  • Composite solid electrolyte membrane, preparation method thereof and solid-state battery

    CN110581311A

  • Composite solid electrolyte membrane, preparation method thereof and lithium ion battery

    CN115395079A

  • Composite solid electrolyte membrane with multilayer structure, preparation method thereof and solid-state battery

    CN110581314A

  • In-situ polymerization solid-state battery with multi-layer structure electrolyte and preparation method of in-situ polymerization solid-state battery

    CN114335716A

  • Ultrathin gradient three-layer solid electrolyte and preparation method and application thereof

    CN114843593A

Cited By

  • Composite solid electrolyte membrane and preparation method and application thereof

    CN121097184A

  • Pebax / PEO composite solid-state battery and preparation method thereof

    CN122177898A